The Intercept : Jeremy Fisk #1 - Wolf, Dick (New York : William Morrow, 2013)
"An adrenaline-fueled thriller debut in the tradition of Three Days of the Condor from the famed creator of TV's Law & Order, featuring NYPD Special Agent Jeremy Fisk, who is New York City's last hope against an ingenious, multi-pronged terrorist attack"--.
Keywords: Police -- New York (State) -- Fiction; Terrorism -- Prevention -- Fiction; FICTION / Thrillers; Suspense fiction